Desulfovibrio alaskensis prophages and their possible involvement in the horizontal transfer of genes by outer membrane vesicles - Crispim, Josicelli Souza; Dias, Roberto Sousa; Laguardia, Clara Nogueira; Araújo, Larissa Cristina; Silva, Jéssica Duarte da; Vidigal, Pedro Marcus Pereira; Sousa, Maíra Paula de; Silva, Cynthia Canêdo da; Santana, Mateus Ferreira; Paula, Sérgio Oliveira de; Sousa, Maíra Paula de (Gene, 2019)
Desulfovibrio alaskensis is a Gram-negative bacterial species that belongs to the group of Sulphate Reducing Bacteria (SRB) and presents prophages in genomes, a common characteristic of the genus Desulfovibrio. Genetic material can be transported by outer membrane vesicles, however, no data regarding the production of these vesicles has been reported for D. alaskensis. To verify the expression of D. alaskensis prophages and their involvement with outer membrane vesicles, the DSM16109 strain was used. The DSM16109 strain had three prophages and presented reduced growth after mitomycin C addition when compared to the control culture. This reduction was accompanied by the presence of virus-like particles (VLPs), indicating mitomycin C dependent prophage induction. The increase in the number of cap gene copies and transcriptions of the three prophages was verified in the control sample, however, without the formation of VLPs. Prophage genes were identified in outer membrane vesicles from cultures treated and not treated with mitomycin C. DSM16109 prophages are expressed spontaneously but only in the presence of mitomycin C was it possible to observe VLP formation. Due to the genetic material detection from the prophages within outer membrane vesicles, this property may be related to the horizontal transfer of viral genes.
Keywords: Bacteriophage; Mitomycin C; Sulphate reducing bacteria